Asplenium danxiaense sp. nov. (Aspleniaceae, Aspleniineae), a new tetraploid fern species from Guangdong, China, based on morphological and molecular data - Xu, Ke-Wang; Lin, Chen-Xue; Guo, Jian-Qiang; Zhou, Xin-Xin; Liao, Wen-Bo; Mao, Ling-Feng (European Journal of Taxonomy, 2022)
The Asplenium coenobiale complex is distributed in Eastern Asia and Southeast Asia with its distribution center in southwestern China. In this study, we carried out a detailed morphological, cytological, and phylogenetic study by adding two samples from Danxia landform in Guangdong. The sequences of five chloroplast markers and one nuclear marker of the A. coenobiale complex were analyzed with maximum likelihood and Bayesian inference, respectively. The morphological and phylogenetic analyses support the recognition of a new species (A. danxiaense K.W.Xu sp. nov.) of the A. coenobiale complex from a cave of Danxia mountain, Guangdong province, southern China. This new species can be distinguished from A. coenobiale and A. pulcherrimum by having scales narrowly triangular to lanceolate, apex ending in a short apical tail, basal basiscopic pinnule usually largest, fertile segment scarce, and exospore length usually more than 50 μm and shows significant molecular differences from other species in this complex. A detailed description and illustrations are presented.